Teacher Training On The Maintenance Of Oral Hygiene And Dental Trauma In Children To Improve Oral Health In Madrasah / Ra Mtsi PTPN IV Kebun Balimbingan - Matondang, Siska Ella Natassa; Dohude, Gostry Aldica; Ranu Putra Armidin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Dental caries is a disease that is mostly found in the oral cavity together with periodontal disease, so it is a major problem of dental and oral health. Based on the results of basic health research (RISKESDAS) in 2007 in 28 Indonesian provinces, it was found that the prevalence of caries in Indonesia was 67.4%, while the prevalence of active caries (untreated caries) was 43.4%. Many children have cavities and residual roots. Children are not able to independently maintain the health of their teeth and mouth. Apart from parents, school teachers have a big role in improving children's oral and dental health. The role of the teacher is meaningful in this case, because the teacher will meet almost every day with the child. However, the reality is that school teachers do not have skills in maintaining oral health, and the level of knowledge about oral health is still low. Therefore, community service for children is needed in the form of dental health education and joint tooth brushes. Besides that, skills training on brushing teeth also needs to be carried out for teachers. The aim of this service is to improve children's dental health by providing dental health education, joint brushing and increasing teacher knowledge and skills in helping to brush teeth in school children. The method of implementing community service is in the form of dental health education for children, and conducting training for school teachers on oral and dental health. It is hoped that with the dedication carried out, there will be an increase in dental and oral health in children and an increase in knowledge and skills of school teachers.